2006
DOI: 10.1007/s11103-006-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of early rice stamen development using organ-specific gene expression profiling

Abstract: Elucidating the regulatory mechanisms of plant organ formation is an important component of plant developmental biology and will be useful for crop improvement applications. Plant organ formation, or organogenesis, occurs when a group of primordial cells differentiates into an organ, through a well-orchestrated series of events, with a given shape, structure and function. Research over the past two decades has elucidated the molecular mechanisms of organ identity and dorsalventral axis determinations. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 35 publications
2
36
0
1
Order By: Relevance
“…Our microarray data (Supplemental Table S1) show that all 26 genes are expressed in PMCs, and many of them (such as U78891 and AK070863) are expressed higher in PMCs than in TCP. The expression patterns of these genes from our microarray are consistent with Lu et al (2006) and their suggested role in meiosis.…”
Section: Verification Of Microarray Datasupporting
confidence: 74%
See 3 more Smart Citations
“…Our microarray data (Supplemental Table S1) show that all 26 genes are expressed in PMCs, and many of them (such as U78891 and AK070863) are expressed higher in PMCs than in TCP. The expression patterns of these genes from our microarray are consistent with Lu et al (2006) and their suggested role in meiosis.…”
Section: Verification Of Microarray Datasupporting
confidence: 74%
“…Particularly, Os05g0551700 showed no expression or low expression in any cell type other than PMC, according to Suwabe et al (2008) and Jiao et al (2009). Os07g0693500 showed gradually reduced expression in rice anthers from stage 2 to stage 7, according to Lu et al (2006). These data suggest that trans-zeatin biosynthesis might be reduced in later stages and in the surrounding tapetum.…”
Section: A Global Snapshot Of Plant Hormone Biosynthesis Pathways In mentioning
confidence: 83%
See 2 more Smart Citations
“…However, whereas comparative global expression analysis of the wild type and mutants uncovered many genes acting specifically in early anther development (Zik and Irish, 2003;Hennig et al, 2004;Wellmer et al, 2004;Lu et al, 2006;Alves-Ferreira et al, 2007;Ma et al, 2007Ma et al, , 2008Wijeratne et al, 2007), only a few are functionally characterized. Among the earliest acting genes are those that relate to more general aspects of organ growth like regulating polarity and cell proliferation, such as the related transcription factors JAGGED and NUBBIN (Dinneny et al, 2006;reviewed in Husbands et al, 2009).…”
Section: Introductionmentioning
confidence: 99%